COVID19 associated mucormycosis: Is GRP78 a possible link? - Jyotsna Gumashta; Raghvendra Gumashta (Elsevier, 2021)
This review aimed to study molecular mechanisms for high incidence of life-threatening mucormycosis infection in COVID19 cases during second wave of SARS CoV2 pandemic in India. Hyperglycaemia, impaired immunity, acidosis, raised ferritin, glucocorticoid therapy, and COVID19 specific other factors have been implicated in pathogenesis of COVID19 associated mucormycosis (CAMM). Endoplasmic reticulum chaperone 'Glucose Related Protein 78' (GRP78), also involved in SARS CoV2 entry, is the host receptor for invasion by Mucorales. GRP78 is over-expressed by SARS CoV2, hyperglycaemia and ferritin. Delta variant of SARS CoV2 and indiscriminate use of steroids were distinguishing features of second wave and appear to upregulate GRP78 through intricate interplay between internal and external milieu. Common invasive fungal infections like candidiasis and aspergillosis, not utilizing GRP78 as receptor, were inconspicuous. Further molecular research to unravel mechanisms involved in the pathogenesis of CAMM shall effectively complement existing strategies for its prevention and treatment.